Competitiveness increase of technological business processes of casting production on the basis of AlpHaset process. Issue 2 (April 2020) - Kukartsev, V A; Bashmur, K A; Kukartsev, A V; Tynchenko, V S; Lugovaya, N M; Ogol, A R; Kukartsev, V V
Abstract: The most important task of the transition from a raw material model of the domestic economy to a model of high-tech development is the use of modern innovative technologies in high-tech industries. It is necessary to use effective and most appropriate modern unstable business conditions for enterprises to manage their production business processes to increase the competitiveness of Russian enterprises. In the modern innovation sphere, there are many contradictions. On the one hand, Russia acts on the world market as a state with high scientific and technical potential, and on the other, it is simultaneously characterized as a technologically backward country. The annual review of the World Economic Forum states that Russia continues to move slowly down the competitiveness rating of the countries of the world. According to the World Economic Forum report, Russia is in only eight of the ten countries in terms of the quality of state institutions and the ability to generate technological innovations. Analysis of the state of the innovation sphere in Russia indicates extremely low rates.